SOCIAL AND ECONOMIC ASPECTS OF FORMING THE FOREST INDUSTRIAL CLUSTER OF THE OMSK REGION ON THE BASIS OF THE IMPORT SUBSTITUTION MECHANISM - S. M. Khairova; B. G. Khairov (Вестник СибАДИ)
In modern conditions of globalization, there is a need to introduce effective integration form in the domestic economy as clusters. Existing methods of  managing the formation of cluster structures in the regions of Russia have  their own characteristics in conditions of turbulence and external influences. In modern science, the issue of identifying priority system- forming elements that form the core of the development and interaction of  economic entities in the region has not been adequately addressed. At  present, the problems of creating an innovative instrument for managing  cluster structures in the regions of the Russian Federation are becoming  topical. The timber industry complex has a national economic significance for Russia. In the article prospects of organizational development of an industrial cluster are considered. The key domestic and foreign markets and  the main consumers of industrial cluster products are researched. The  characteristics of the current state of the industrial potential of the members of the timber industry cluster are given. Prospects for the development of the Timber Industry Cluster of the Omsk Region have been identified, which  directly depend on the construction of sustainable cooperative ties. The  socio-economic aspects of the formation of the timber industry cluster of the  Omsk Region are considered. The peculiarities of import substitution in  clusters are revealed. It is assumed that effective use of the import substitution mechanism will allow to optimize the interaction of the economic entities of the region on the basis of the priority economic cluster,  which will lead to an increase in the social and economic efficiency of the  regions of Russia and will help to smooth the gap between the development of the regions.